The use of transitive Montgomery indicators for scanner data analysis - Białek, Jacek; Pawelec, Natalia (Publishing House of Wroclaw University of Economics and Business, 2024)
Although the modern price index theory is based on an analysis of ratios of prices and quantities, one may be often more interested in working with differences in these values in many economic areas, e.g.: revenue change decompositions, profit and cost change decompositions, or an analysis of changes in consumer surplus. The benefit of using these differences is that there is no problem associated with the occurrence of zero prices and quantities, a problem that arises when working with ratios. In practice, one mostly cares about decomposing the value difference into indicators of contributions from price and quantity differences. The well-known price and quantity indicators are the Bennet and the Montgomery indicators, which are not transitive. This paper revises the price and quantity Montgomery indicators and their multilateral versions for the analysis of scanner data. Specifically, instead of considering ‘classical’ comparisons across firms, countries or regions, the transitive versions of the Montgomery indicators were adapted to work on scanner data sets observed over a fixed time window. One of the objectives of the study was to compare bilateral and multilateral Montgomery indicator values for different data aggregation levels and three main types of data filters. To the best of the authors’ knowledge, this study is pioneering on the grounds of implementing the multilateral Montgomery indicators in scanner data analysis.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 1-13
Keywords: scanner data; Montgomery indicators; transitivity; multilateral indicators